2020
DOI: 10.1016/j.omto.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Dehydrogenase A Depletion Alters MyC-CaP Tumor Metabolism, Microenvironment, and CAR T Cell Therapy

Abstract: To enhance human prostate-specific membrane antigen (hPSMA)-specific chimeric antigen receptor (CAR) T cell therapy in a hPSMA + MyC-CaP tumor model, we studied and imaged the effect of lactate dehydrogenase A (LDH-A) depletion on the tumor microenvironment (TME) and tumor progression. Effective LDH-A short hairpin RNA (shRNA) knockdown (KD) was achieved in MyC-CaP:hPSMA + Renilla luciferase (RLuc)-internal ribosome entry site (IRES)-GFP tumor cells, and changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…4Ab,c and 4Db,c). A Weka analysis (28) showed signi cantly greater LDH-A staining in both GL261 and CT2A NC tumors compared to the LDH-A KD tumors (Fig. 4B, 4E, Table S-1), consistent with the Western blot and LDH enzyme results (Fig.…”
Section: Ldh-a and Ldh-b Tumor Staining Patternssupporting
confidence: 84%
See 2 more Smart Citations
“…4Ab,c and 4Db,c). A Weka analysis (28) showed signi cantly greater LDH-A staining in both GL261 and CT2A NC tumors compared to the LDH-A KD tumors (Fig. 4B, 4E, Table S-1), consistent with the Western blot and LDH enzyme results (Fig.…”
Section: Ldh-a and Ldh-b Tumor Staining Patternssupporting
confidence: 84%
“…Stably transduced clones (KD cell lines) were developed, along with a control (NC) cell line bearing a scrambled shRNA. Based on the previous experience (12,28), we decided to use the most effective shRNAs (shRNA-2) to develop LDH-A KD cells in murine glioma cells. The transfection of GL261 cancer cells with shRNA-2 resulted in a signi cant knock-down effect for LDH-A (approximately 10% of that in wild type cells), while bulk CT2A and ALTS1C1 cells transfected with shRNA-2 had a signi cantly less level of LDH-A knock-down (40-60%).…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst little is known about the direct influence of lactate on CAR-T cell metabolism and function, in an attempt to overcome the suppressive properties of lactate, studies have begun to investigate the mechanistic effect of lactate dehydrogenase (LDH) inhibition. Specifically, the inhibition of LDH enhances the CAR-T cell function [ 47 , 48 ], in particular one study identified a synergistic effect with IL-21 to promote CAR-T memory and enhanced downstream anti-tumour immunity [ 48 ].…”
Section: Current Metabolic Conditioning Of Car-t Cellsmentioning
confidence: 99%
“…Treg are oxidative and can take up and consume lactate in the TME [ 152 , 153 ]. Clinically, levels of lactate dehydrogenase A (LDH-A), which converts pyruvate into lactate, correlate with worse clinical outcomes and fewer infiltrating T cells in multiple cancer types [ 148 , 154 , 155 ].…”
Section: Introductionmentioning
confidence: 99%